7-Methoxy-8-Prenylated Coumarins from Murraya koenigii (Linn.) Spreng. (Dhaka University Journal of Pharmaceutical Sciences, 2017)
Four coumarin derivatives were isolated from the methanol extract of stem bark of Murraya koenigii (Linn.) Spreng. Extensive spectroscopic studies, including high field NMR analyses allowed to identify these compounds as meranzin hydrate (1), epoxyosthol (2), isomeranzin (3) and murracarpin (4). The identity of the compounds was confirmed by comparison with published data as well as co-TLC with authentic samples. This is the first report of occurrence of meranzin hydrate (1), epoxyosthol (2) and isomeranzin (3) from M. koenigii.Dhaka Univ. J. Pharm. Sci. 15(2): 155-159, 2016 (December)